A Statistical Analysis on The Effects of a Nation’s Individual Network Usage on A Business’s Capacity for Innovation - Alba, Muhammad C. (International Journal of Social Sciences and Management, 2020)
Correction: At the request of the author, on 17th October 2022, the name of the author was changed FROM Charles Alba TO Muhammad C. Alba. In this paper, we aimed to look at a Nations Individual Network usage and its effects on a business’s capacity for innovation. We do so through the utilization of data from 2016 World Economic Forum (WEF) Networked Readiness Index report. In order to best determine the effects of a Nations Individual Network usage on a business’s capacity for innovation, we create the most suitable supervised Machine Learning model through stepwise regression. We did so with the use of the numerous variables in the 6th pillar of the Network Readiness report, which reflect a nations individual network usage, against the Capacity for innovation Index found in the 7th pillar of the Network Readiness Index. Of the 6 initial prior variables in the 6th Pillar reflecting Individual Network Usage, stepwise regression outputs a best fit and an appropriate model that contains predictors “Use of virtual social networks”, “Rate of Mobile broadband subscriptions” and “Rate of Mobile phone subscriptions” as significant factors in predicting a Business’s Capacity for innovation. The results are utilized to make policy-proposals to both governments and businesses with the aim of improving a nations Business’s Capacity for Innovation. Int. J. Soc. Sc. Manage. Vol. 7, Issue-3: 113-130